Balancing services from built and natural assets via river basin trade-off analysis - Hurford, A.P.; McCartney, Matthew P.; Harou, Julien J.; Dalton, J.; Smith, Mark; Odada, E. (Elsevier, 2020)
Built water infrastructure impacts the balance of services provided by a river and its flow regime. Impacts on both commercial and subsistence activities should be considered in water management decision-making. Various methods used to define mandatory minimum environmental releases do not account for the inherent and often complex trade-offs and synergies which must be considered in selecting a balance of ecosystem and engineered services. This paper demonstrates the value and use of optimised many-objective trade-off analysis for managing resource-systems providing diverse and sometimes competing services. Using Kenya’s Tana River basin as a demonstration it shows controlled releases from multi-reservoir systems can be optimised using multiple performance metrics, representing individual provisioning ecosystem and engineered services at different locations and relating to different time periods. This enables better understanding the interactions between natural and built assets, and selecting river basin interventions that appropriately trade-off their services. Our demonstration shows prioritising Kenya’s statutory minimum environmental ‘reserve’ flows degrades flood-related provisioning services. Low overall flow regime alteration correlates neg